2010
DOI: 10.1007/s11274-010-0466-8
|View full text |Cite
|
Sign up to set email alerts
|

Determination of genetic variability among the isolates of Metarhizium anisopliae var. anisopliae from different geographical origins

Abstract: The entomopathogenic fungus Metarhizium anisopliae is currently used as an efficient biological control agent against different insects. The prevalence and genetic variability of the entomopathogenic fungus Metarhizium anisopliae var. anisopliae in Asian countries (China, Laos, Singapore and South Korea) and a European country (The Netherlands) was examined. The fungus was found to be widespread in agricultural and forest soils throughout China especially in the south and south western regions, with a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
0
22
0
10
Order By: Relevance
“…There was no correlation between groups and host or geographic origin. SSR markers (Ma097,099,142,145,164,165,195,210,307,325,327,and 375) were used in studying polymorphism in isolates of M. anisopliae from soil samples (80%) and insects (20%) from different regions of Chile (Velásquez et al, 2007) and soil samples (forest and agriculture) from countries in Asia and Europe (Freed et al, 2010). The authors observed the formation of three groups and a slight variation among the populations (18.5 and 19.35%), and there was no association between genetic diversity and the collection sites for the different isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no correlation between groups and host or geographic origin. SSR markers (Ma097,099,142,145,164,165,195,210,307,325,327,and 375) were used in studying polymorphism in isolates of M. anisopliae from soil samples (80%) and insects (20%) from different regions of Chile (Velásquez et al, 2007) and soil samples (forest and agriculture) from countries in Asia and Europe (Freed et al, 2010). The authors observed the formation of three groups and a slight variation among the populations (18.5 and 19.35%), and there was no association between genetic diversity and the collection sites for the different isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Group I introns, found in rDNA genes of eukaryotes, usually have irregular distribution, being present in some isolates and absent in others, which can become a source of genetic variability (Mavridou et al, 2000). Markers such as RAPD (random amplified polymorphic DNA), SSR (simple sequence repeats) and AFLP (amplified fragment length polymorphism) have also been deployed in genetic variability studies of isolates of M. anisopliae from different hosts and geographic origins (Velásquez et al, 2007;Inglis et al, 2008;Freed et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…M. anisopliae var. anisopliae is a globally distributed, generalist parasite, found in the region where P. dives occurs, and known to infect numerous ant species as well as many other insects (Schmid-Hempel, 1998;Freed et al, 2011;Boucias and Pendland, 1998;Dong et al, 2009;Sun and Liu, 2008;Hughes et al, 2004a). It is thus highly likely to represent a natural threat to P. dives, but one which will not have coevolved to exploit any particular host species.…”
Section: Methodsmentioning
confidence: 99%
“…These markers were used to examine polymorphism in M. anisopliae, but the primers used to examine samples derived from soil cores from different regions in Chile (VELÁSQUEZ et al, 2007) and numerous countries in Asia and Europe (FREED et al, 2010) were not effi cient in detecting informative polymorphisms. To the contrary of microsatellite analysis, the ISSR technique amplifi es fragments located between two repetitive regions present in various genomes (FALEIRO 2007), known as inter-microsatellite regions.…”
Section: Molecular Characterizationmentioning
confidence: 99%